A contribution to the systematics and biology of Nudaurelia cytherea (Fabr.) (Lepidoptera: Saturniidae) - Geertsema, H.(Hendrik) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1970.